2004
DOI: 10.2478/v10050-008-0059-1
|View full text |Cite
|
Sign up to set email alerts
|

Speed of autumn migration of the Blue Tit (Parus caeruleus) along the eastern and southern Baltic coast

Abstract: Speed of autumn migration of the Blue Tit (Parus caeruleus) along the eastern and southern Baltic coast An analysis of the speed of autumn migration was based on 315 ringing recoveries of Blue Tits caught between 1963-1999 at 6 ringing stations along the south-eastern and southern Baltic coast. It was found that among passerines the Blue Tit is the slowest European migrant (median value - 25.8 km/day, average - 28.4 km/day), with a very low (intra- and interpopulation) variation of migration speed. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…The mass-scale migration of birds (including Robins) over an area of several hundred square kilometres has been well documented (Žalakevičius 1990(Žalakevičius , 1994(Žalakevičius , Žalakevičius & Petraitis 1992(Žalakevičius , Švažas 1993. Also Nowakowski (2001) showed that Great Tits Parus major do indeed seem to synchronise the speed of migration on the large scale if passage is intensive.…”
Section: Discussionmentioning
confidence: 98%
“…The mass-scale migration of birds (including Robins) over an area of several hundred square kilometres has been well documented (Žalakevičius 1990(Žalakevičius , 1994(Žalakevičius , Žalakevičius & Petraitis 1992(Žalakevičius , Švažas 1993. Also Nowakowski (2001) showed that Great Tits Parus major do indeed seem to synchronise the speed of migration on the large scale if passage is intensive.…”
Section: Discussionmentioning
confidence: 98%
“…1; for description of stations and field methods see Busse 2000 andNowakowski 2001). I also referred to 218 recoveries of birds ringed at the Ventes Ragas and Neringa stations (published in Patapavièius 1982, 1983, 1986a, 1986b, 1986c, 1987, 1988, 1989, Skuodis and Kurpyté 1989 and in Rybachy (in Bolshakov et al 1999Bolshakov et al , 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The speed of movement of Great Tits in the described region is relatively stable, at 33.2 km/day on average (Nowakowski 2001). It is thus possible to standardise seasonal migration dynamics at different stations (by presenting them in standardised days of passage).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations